Macrophages with Different Polarization Phenotypes Influence Cementoblast Mineralization through Exosomes - Yi Zhao; Yiping Huang; Hao Liu; Kuang Tan; Ruoxi Wang; Lingfei Jia; Weiran Li (Hindawi Limited, 2022)
Root resorption is a common dental challenge that can lead to tooth loosening or even tooth loss. Among the cells involved in root resorption, cementoblasts are responsible for laying down the cementum, while macrophages with different phenotypes have also been shown to have bidirectional effects on root resorption. However, the relationship between macrophages and cementoblasts remains largely unknown. In this study, we examined the effect of macrophages with different polarization phenotypes on the mineralization of cementoblasts. Using the transwell coculture system and a conditioned medium-based coculture system, we found that compared with M0 (unpolarized macrophages), M1-polarized macrophages attenuated cementoblast mineralization, while M2-polarized macrophages enhanced cementoblast mineralization. Furthermore, by extracting M0/M1/M2 macrophage exosomes and examining their effects on the mineralization of cementoblasts, we found that the effects of macrophages on cementoblast mineralization were, at least partially, exerted by exosomes. Moreover, in vivo studies also indicated that an increased M1/M2 ratio could suppress cementoblast mineralization and bring about root resorption. During mechanical force-induced orthodontic tooth movement (OTM), root resorption was evident on the compression side of periodontal tissue, and a higher M1/M2 ratio and weaker cementoblast mineralization were observed on the compression side than on the tension side. We also used localized lipopolysaccharide (LPS) injection to increase the M1/M2 ratio around the roots of maxillary molars, where root resorption and decreased cementoblast mineralization were also observed. Furthermore, when we injected the exosomes from M0 and M1- and M2-polarized macrophages into mice, it was observed that the cementoblast mineralization was attenuated in the group injected with M1-polarized macrophage exosomes, while it was augmented in the group injected with M2-polarized macrophage exosomes.